GSDME knockout alleviates hematopoietic stem cell irradiation injury and aggravates myeloid-biased differentiation - Su, Lulu; Dong, Yinping; Guan, Bowen; Wang, Yuquan; Lu, Yanhua; Wang, Xinyue; Li, Wenxuan; Huo, Qidong; Meng, Aimin; Li, Deguan (Frontiers in Cell and Developmental Biology, 2025)
BackgroundBone marrow (BM) suppression is the most prevalent dose-limiting side effect of chemotherapy and radiotherapy. Exposure to ionizing radiation (IR) results in acute BM suppression and long-term BM injury. Gasdermin E (GSDME) is crucial for mediating apoptosis and pyroptosis during chemotherapy. However, its role in radiation-induced hematopoietic injury is not well established. Therefore, we aimed to investigate the role of GSDME on radiation-induced hematopoietic injury.MethodsWe established hematopoietic radiation injury models in C57BL/6 mice and Gsdme−/− mice. The peripheral blood (PB) counts, phenotypes of BM cells and spleen cells were analyzed. The colony-forming unit-granulocyte and macrophage assays and competitive repopulation assays were measured to evaluate the function of hematopoietic cells.ResultsWe demonstrated that GSDME regulates the survival and differentiation of hematopoietic stem cells (HSCs). The knockout of GSDME reduced the number and proliferation of HSCs and shortened the survival time of mice post IR. Additionally, GSDME knockout protected LSK (Lin-Sca1+c-kit+) cells, long-term HSCs (LT-HSCs), granulocyte–monocyte progenitors (GMPs), and myeloid cells (M cells) from IR injuries during acute BM suppression. Furthermore, GSDME knockout protected LSK cells, LT-HSCs, GMPs and M cells, alleviated the proliferation inhibition of hematopoietic progenitor cells (HPCs) and exacerbated lymphocyte damage during long-term BM injury.ConclusionGSDME is vital for the survival and differentiation of HSCs, and its absence promotes myeloid-biased differentiation postirradiation. These findings highlight the critical role of GSDME in radiation-induced hematopoietic injury, particularly in the myeloid differentiation of HSCs.